The Association Between Gender and Complications of Type 2 Diabetes Mellitus Among Patients in Almarj City-Libya - Ehmaida, Fatma KH. Ali; Hemdan , Sokaina Saad; Aljebaly, Asmaa M. (Al-Mukhtar Journal of Sciences, 2020)
This study was carried out to provide new data on patients with type 2 diabetes mellitus and any suggestions for the prevention of what is a life-threatening disorder. Four hundred and seventy-three type 2 diabetic mellitus patients from Almarj general hospital were used: (222) females and (251) males for the period from October -2017 to April – 2018.The study focused on the relationship between genders and complications of diabetes mellitus. The study showed no significant differences (P > 0.05) between hypertension, heart disease, respiratory dysfunction, nephropathy, urinary tract infection, anemia, hypothyroidism, diabetic ketoacidosis, gastric infection, and gender. On the other hand, a significant (P ≤ 0.05) relationship was found between hepatopathy and foot complications and gender. Findings showed that males with the risk of the dangers of type 2 diabetes mellitus complications were more than females in Almarj city.